2009
DOI: 10.1128/jcm.01602-08
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Identifying Common and Distinct Sequences among Texas Clinical Strains of Mycoplasma genitalium

Abstract: Mycoplasma genitalium is associated with numerous human genitourinary tract maladies, including nonchlamydial, nongonococcal urethritis in men and cervicitis, endometritis, and pelvic inflammatory disease in women (1,4,5,12,19,29,30,35,39). Understanding the epidemiological aspects of infections and developing effective treatment require reliable typing of pathogenic microorganisms. Since M. genitalium is very difficult to culture from clinical specimens (13, 21), classical microbiological typing methods are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…In comparison, the mgpB SNP typing resulted in amplification of DNA from 96 % of the specimens, higher than the percentage reported in a recent study using this typing method (38.9 %) (Musatovova & Baseman, 2009). Ma et al (2008) had already applied nested PCR to those specimens for which the initial PCR products were not visible or very faint on agarose gels.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In comparison, the mgpB SNP typing resulted in amplification of DNA from 96 % of the specimens, higher than the percentage reported in a recent study using this typing method (38.9 %) (Musatovova & Baseman, 2009). Ma et al (2008) had already applied nested PCR to those specimens for which the initial PCR products were not visible or very faint on agarose gels.…”
Section: Discussionmentioning
confidence: 59%
“…We used the numbering system developed originally in 2006 by Hjorth et al (2006) with the description of 56 STs, numbered 1-56. In addition to the 56 STs, we successively included the seven new STs described by Ma et al (2008), numbered 57-63, and the 17 new STs described by Musatovova & Baseman (2009), numbered 64-80. In our study, we then described eight new STs of the mgpB gene, numbered 81-88, and deposited them in GenBank under the accession numbers HM565865-HM565872, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbiol., 10 (6): 260-269, 2015 In a previous study, Kenri et al (2012) reported that Mycoplasma pneumoniae strain 309, a type 2a (subtype 2 variant) strain, has variations in the P1 protein, which is responsible for the attachment of this bacterium to the host cells. Furthermore, Musatovova and Baseman (2009) identified common and distinct sequences among the Texas clinical strains of Mycoplasma genitalium and obtained 18 DNA sequence variants, which were compared with all the other available clinical sequences. A detailed analysis revealed silent mutations of six amino acid residues within the encoded region of the MgPaadhesin in numerous clinical strains.…”
Section: Resultsmentioning
confidence: 99%